Aproximación de gobernanza como conflicto ambiental. Caso arco minero del orinoco (Agroindustria, Sociedad y Ambiente, 2018)
In 2008, the creation of the Orinoco Mining Arc (AMO) was ordered, but its start-up and exploitation was halted due to the pressure exerted by the communities in the area. The instrument used is the "Development Zone Strategic National AMO ". The objective is the approximation of the non-compliance of the Governance in the case of the AMO. The method was qualitative-documentary. It was found that the problem goes beyond sustainability and economy, being the way of Government how to give ecological answers to the global warming through the discourse that the climate was not changed but if they could change the systems to help the sustainable development, it that currently the use of the terms endogenous or sustainable are without force with the measures of the decrees without taking into account what they promulgated. De esta manera se pone en duda la credibilidad de Gobernanza yendo en contra de la Nación en la muerte ambiental y la contaminación como del Río Orinoco, contradiciendo el Objetivo 5 del Plan de la Patria que plantea la preservación de la vida en el planeta y salvar la especie humana, mediante la construcción del modelo económico productivo Ecosocialista
Keywords: Environment; decree; ecosocialismo; government and model